Ankle joint pressure change before and after subtalar joint arthrodesis in varus and valgus malalignment of the tibia. (21st April 2022) - Hu, Mu; Xu, Xiangyang; Mei, Jiong
Purpose: The compensation mechanism of subtalar joint in ankle with varus or valgus deformity is controversial and not well established. This biomechanical study aims to investigate how subtalar joint arthrodesis will affect the ankle joint pressure in varus and valgus malalignment of the tibia.Methods: Eight fresh-frozen human cadaver legs were tested in this study. A custom-made fixture was utilized and a total of 600N was applied to simulate weight-bearing. Intra-articular sensors (TeckScan) were inserted in the ankle joint to demonstrate the ankle joint pressure. Conditions include: Neutral, 5°, 10°, 15° and 20° varus, 5°, 10°, 15° and 20° valgus.Results: After the fusion of the subtalar joint, when the tibia is gradually inverted, the inside pressure of the ankle joint gradually increases, and the pressure on the outside of the ankle joint gradually decreases. When the tibia is gradually eversion, the pressure on the outside of the ankle joint gradually increases, and the inside of the ankle joint gradually decreases.Conclusions: After the subtalar joint is fused, the compensatory activity of the subtalar joint disappears, and the regulation of the pressure in the ankle joint will be lost. We hypothesized that the inversion compensation of the subtalar joint is more likely to occur than the eversion compensation.